Issues of Improving the Operations of Commercial Banks in the Securities Market - Akmal Ruzimamatovich Norov; Nodir Muratovich Shamsiyev; Muzrof Yusup ugli Xolbozorov; Anvar Ruzimamatovich Norov; Fayozjon Farxod ugli Rakhmatullaev (Universitas Muhammadiyah Sidoarjo, 2022)
This article examines the nature and characteristics of home securities market, location and the operations of commercial banks in this market. The article, using the method of comparative analysis revealed a flaw in the operations of commercial banks in the securities market and developed proposals for its positive decisions.